Innovation in Preschool and Early School Education - Miłek, Katarzyna (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
The importance of innovation in early childhood learning emphasizes the need for a responsive approach to local cultural riches and values. The local wisdom approach emerges as a promising paradigm, creating space for innovation that has a positive impact on learning management. The aim of this research is to describe, analyze and offer learning innovation solutions through a local wisdom approach in a management context. The research method used is literature study, through collecting library data originating from articles, journals, electronic books and relevant document data related to the research focus. The data analysis process was carried out using descriptive methods to analyze the material collected. The research results show that innovative learning with local wisdom creates an interesting learning environment and supports children's development by enriching their experience of local values ​​and traditions. Innovative activities include learning methods, creative management, material development, and local community empowerment.